2009
DOI: 10.3348/kjr.2009.10.2.112
|View full text |Cite
|
Sign up to set email alerts
|

SPIO-Enhanced MRI Findings of Well-Differentiated Hepatocellular Carcinomas: Correlation with MDCT Findings

Abstract: ObjectiveThis study was designed to assess superparamagnetic iron oxide (SPIO)-enhanced MRI findings of well-differentiated hepatocellular carcinomas (HCCs) correlated with their multidetector-row CT (MDCT) findings.Materials and MethodsSeventy-two patients with 84 pathologically proven well-differentiated HCCs underwent triple-phase MDCT and SPIO-enhanced MRI at a magnetic field strength of 1.5 Tesla (n = 49) and 3.0 Tesla (n = 23). Two radiologists in consensus retrospectively reviewed the CT and MR images f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 34 publications
2
25
0
Order By: Relevance
“…All MRI experiments were performed with a Magnetom Vision 1.5 T (Siemens, Germany). Typical imaging parameters for in vivo imaging of cerebral anatomy used a multiple spin-echo sequence and T2 weighted sequences, which have been previously used for detection of SPIO-labeled cells [6,12,19], to assess MRI sensitivity of MIRB-labeled cMSCs.…”
Section: Mrimentioning
confidence: 99%
“…All MRI experiments were performed with a Magnetom Vision 1.5 T (Siemens, Germany). Typical imaging parameters for in vivo imaging of cerebral anatomy used a multiple spin-echo sequence and T2 weighted sequences, which have been previously used for detection of SPIO-labeled cells [6,12,19], to assess MRI sensitivity of MIRB-labeled cMSCs.…”
Section: Mrimentioning
confidence: 99%
“…It is reported that about 40% of HCCs lack the arterial-phase hyperenhancement, which includes most early HCCs (Fig. 3) [57,58]. This can lead to a misdiagnosis, using extracellular contrast agents, of nondefinitive HCC.…”
Section: Imaging-based Characterization Of Borderline Hepatic Nodulesmentioning
confidence: 99%
“…In our study, hyperintensity was observed in 12 nodules (16%) on SPIO‐enhanced T2‐weighted MRI. In several previous studies, 15–85% of well‐differentiated HCCs were hyperintense, as observed on SPIO‐enhanced T2‐weighted MRI . Most hypovascular nodules showing hypointensity during the HBP on Gd–EOB–DTPA‐enhanced MRI are regarded as well‐differentiated HCCs.…”
Section: Discussionmentioning
confidence: 80%
“…Superparamagnetic iron oxide (SPIO) is a liver‐specific contrast agent that is taken up by Kupffer cells and is a clinically useful method in the diagnosis of HCC . Malignant tumors generally lack Kupffer cells and appear to be hyperintense against the hypointense background of the surrounding normal hepatic parenchyma . The use of SPIO for detecting well‐differentiated HCCs is limited owing to the retained Kupffer cell activity within the tumor, although 15–85% of well‐differentiated HCCs have been reported to be hyperintense, as evidenced by SPIO‐enhanced T2‐ and T2 * ‐weighted MRI .…”
Section: Introductionmentioning
confidence: 99%